Understanding Of Sharia Contracts Among Msme Actors - Khoirudin; MHD. Nanang Hidayat; M.Ilham; Muhammad Fakhri Khairi (LP2M IAIN Palopo, 2026)
Understanding sharia contracts is an important aspect in supporting MSME business practices in accordance with Islamic economic principles. However, in practice, many MSME actors take advantage of sharia financing without an adequate conceptual understanding of the contracts used. This study aims to analyze the level of understanding of MSME actors on the concept, principles and mechanisms of sharia contracts, the factors that affect them and their implications for business management and financial decision-making. The research uses the literature review method by examining various scientific journals and academic publications related to Islamic financial literacy, sharia financing and the implementation of contracts in MSMEs. Analysis is carried out through content analysis and narrative synthesis to find patterns of findings, similarities, differences and research gaps. The results of the study show that the level of understanding of sharia contracts for MSME actors is still relatively low to moderate and tends to be terminological and procedural. Influencing factors include Islamic financial literacy, education and education, business experience, the role of Islamic financial institutions, managerial capacity and business digitalization dynamics. A good understanding of contracts has been proven to have implications for the suitability of business practices with sharia principles, more structured financial management, understanding of business risks and more rational financing decisions. This research emphasizes the importance of strengthening literacy and sustainable mentoring so that the understanding of sharia contracts can be internalized in the business behavior of MSMEs and support the sustainability of sharia-based businesses.